SARS CoV-2 AND OTHER REVERSE ZOONOSES: UNDERSTANDING THE HUMAN ANIMAL INTERFACE FOR DEVISING CONTROL STRATEGIES - Sophia Makdoh Gogoi; Himasri Das; Syed Abdul Arif; Chandrani Goswami; Tinku Das; Durlav Prasad Bora; Pankaj Deka; Samsun Neher; Sutopa Das; Girindra Kumar Saikia (Journal of Animal and Plant Sciences, 2023)
Destructive human activities have been ravaging nature and have also in certain situations paved the way towards emergence of diseases hitherto unknown. While a substantial number of the emerging diseases are known to originate from animals, there are many instances where humans have been responsible for causing infection in animals. Such “spill over” encountered in SARS CoV-2 raises alarm as it complicates the process of understanding the disease dynamics. Many other pathogens have been known to cause reverse zoonoses including Influenza viruses. The knowledge that have been gathered throughout the years from previous such occurrences can help the scientific community in designing the control and preventive protocols for arresting the spread of SARS CoV-2 among the human and animal population. In humans extensive vaccination is being practiced as an effective intervention strategy and the reverse zoonotic nature of the virus has given an impetus for assessing the feasibility of using similar vaccines in animals. However, to break the reverse zoonotic cycle capable of causing pandemics, a holistic approach is required to understand the pathogen movement at the man-animal interface which not only includes the viral properties like mutation rate, virulence characteristics etc but various other factors such as environmental changes, human interference etc. Effective biosecurity measures, artificial intelligence based monitoring systems and robust molecular epidemiological surveillance can help in preventing as well as predicting “spillover” of pathogens which will be critical for preventing pandemics in future.
Keywords: SARS CoV-2; Anthroponosis; Reverse zoonoses; Spill over; Emerging diseases